2020
DOI: 10.1186/s12884-020-03219-w
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum uterine activity and neonatal outcomes: a systematic review

Abstract: Background Increased uterine activity (UA) may not allow adequate recovery time for foetal oxygenation. Methods The aim of the study was to determine if increased UA during labour is associated with an increased risk of either short- or long-term neurological injury in term neonates, or with neonatal proxy measures of intrapartum hypoxia-ischemia. MEDLINE, CINAHL, and ClinicalTrials.gov were searched using the following terms: uterine activity, excessive uterine activity, XSUA, uterine hyperstimulation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…The duration of the spiral artery compression depends on the strength and the duration of the contraction. In a recent systematic review by Reynolds et al, an increased uterine activity was found to be a non-specific predictor of depressed Global Journal of Reproductive Medicine neurological function in the newborn [1]. Similarly, it has been shown that six or more contractions in 10 minutes were significantly associated with fetal heart rate decelerations (P ≤ .001) [2].…”
Section: Introductionmentioning
confidence: 94%
“…The duration of the spiral artery compression depends on the strength and the duration of the contraction. In a recent systematic review by Reynolds et al, an increased uterine activity was found to be a non-specific predictor of depressed Global Journal of Reproductive Medicine neurological function in the newborn [1]. Similarly, it has been shown that six or more contractions in 10 minutes were significantly associated with fetal heart rate decelerations (P ≤ .001) [2].…”
Section: Introductionmentioning
confidence: 94%
“…Other factors need also to be considered in the context of studying labour duration; uterine contractions cause intermittent decreases in uteroplacental blood flow, resulting in temporarily reduced blood and oxygen delivery to the fetus 39 , 40 . Most fetuses tolerate these normal labour processes very well.…”
Section: Commentmentioning
confidence: 99%
“…Слабкість пологової діяльності (СПД) спричиняє збільшення тривалості пологів, підвищує ризик оперативного вагінального розродження, кесаревого розтину та післяпологових кровотеч [3][4][5][6][7][8]. Надмірно сильна пологова діяльність або гіпертонічна дисфункція матки (ГДМ) має суттєвий негативний вплив як на матір (травми матки та пологових шляхів, емболія навколоплодовими водами, післяпологові кровотечі), так і на новонародженого (гіпоксія, внутрішньочерепні крововиливи, травми) [2,[8][9][10][11][12][13].…”
Section: вступunclassified